PENGARUH PROFITABILITAS, LEVERAGE DAN NILAI PASAR TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR FOOD & BEVERAGE DI BURSA EFEK INDONESIA - Safitri, Kiki Rezky; Oemar, Fahmi; Salmiah, Neneng (Jurnal Akuntansi Kompetif, 2025)
The purpose of this study is to examine how market value, profitability, and leverage affect stock prices in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 timeframe. The Price to Earnings Ratio (PER), which measures market value, the Debt to Equity Ratio (DER), which measures leverage, and Return on Assets (ROA), which measures profitability, are the independent variables employed in this study. The stock price is the study's dependent variable. The study employs a quantitative methodology and uses secondary data from firm financial records obtained through purposive sampling. A total of 24 companies were chosen as samples, and 72 observations were made over the course of three years. Panel data regression analysis using the f test, t test, and coefficient of determination (R2) is the data analysis method employed. The findings indicated that market value (PER) has a substantial positive impact on stock prices, profitability (ROA) has a significant positive impact on stock prices, and leverage (DER) has no significant impact on stock prices. At the same time, market value, profitability, and leverage all have a big impact on stock prices. This study offers useful recommendations for both corporate management in controlling variables that impact stock prices and investors in evaluating the firm's financial performance prior to making an investment